Patent foramen ovale closure vs. medical therapy alone after cryptogenic stroke in China: A cost-effectiveness analysis - Wei, Na; Liu, Bo; Ma, Meijuan; Zhang, Xuejun; Zhang, Wei; Hou, Fangxia; Liu, Fuqiang; Yu, Xiangyou (Frontiers in Public Health, 2022)
Background In 2019, there were 28. 76 million patients with stroke in China, with 25% of them suffering from cryptogenic stroke (CS). Patent foramen ovale (PFO) is related to CS, and PFO closure can reduce recurrent stroke. To date, no study has investigated the cost-effectiveness of PFO closure vs. medical therapy among such populations in China. Methods A Markov model with a cycle length of 3 months was established to compare the 30-year cost-effectiveness of PFO closure and medical therapy. The transition probability of recurrent stroke was derived from the RESPECT study, and the costs and utility were obtained from domestic data or studies conducted in China. The primary outcome of this study was the incremental cost-effectiveness ratio (ICER), which represents the incremental cost per quality-adjusted life year (QALY). PFO closure was considered cost-effective if the ICER obtained was lower than the willingness-to-pay (WTP) threshold of 37,654 USD/QALY; otherwise, PFO closure was regarded as not being cost-effective. One-way and probabilistic sensitivity analyses were performed to test the robustness of the results. Results After a simulation of a 30-year horizon, a cryptogenic stroke patient with PFO was expected to have QALY of 13.15 (15.26 LY) if he received PFO closure and a corresponding value of 11.74 QALY (15.14 LY) after medical therapy. The corresponding costs in both cohorts are US 8,131 and US 4,186, respectively. Thus, an ICER of 2783 USD/QALY and 31264 USD/LY was obtained, which is lower than the WTP threshold. One-way and probabilistic sensitivity analyses showed that the results were robust. Conclusion With respect to the WTP threshold of three times per capita GDP in China in 2021, PFO closure is a cost-effective method for Chinese cryptogenic stroke patients with PFO, as shown in the 30-year simulation.